Relationships between elite adolescent athletes' perceptions of parental behaviors and their motivational processes: Does sex matter? - Lienhart, N.; Nicaise, V.; Martinent, G.; Guillet-Descas, E.; Bois, J. (International Journal of Sports Science & Coaching, 2019)
This study aimed to: (a) examine the relationships between high-level athletes' perceptions of mothers' and fathers' behaviors, their satisfaction of basic psychological needs, and sport motivation and (b) explore whether the sex of the athlete moderated the aforementioned relationships. A total of 333 adolescent athletes involved in intensive training settings completed the Parental Involvement in Sport Questionnaire (PISQ), the Behavioral Regulation in Sport Questionnaire (BRSQ) and the Basic Need Satisfaction in Sporting Context Scale (BNSSS). Data were examined using correlational analyses and partial least square path modeling (PLS-PM). The PLS-PM revealed that father's perceived pressure positively predicted maladaptive outcomes (controlled forms of motivation and amotivation). Perceptions of the mothers' and fathers' praise and understanding positively predicted adaptive athletes' outcomes (self-determined forms of motivation and satisfaction of competence and relatedness), whereas the mothers' and fathers' perceived pressure negatively predicted such adaptive outcomes. Furthermore, differences regarding the aforementioned relationships between mother's and father's behaviors and athletes' outcomes were highlighted across their sex. More significant relationships emerged for boys versus girls and between athletes' outcomes and the perceived behaviors of the same-sex parents. In particular, the direction of relationships between introjected regulation and two parental behaviors (i.e. perception of father's directive behaviors and perception of mother's pressure) was reversed for boys and girls. As a whole, this study highlighted that both parent's and child's sex should be evaluated to understand sport parenting.